2009
DOI: 10.1111/j.1471-4159.2009.06047.x
|View full text |Cite
|
Sign up to set email alerts
|

BAG‐1M is up‐regulated in hippocampus of Alzheimer’s disease patients and associates with tau and APP proteins

Abstract: The accumulation of tau and amyloid beta proteins is the major molecular pathology of Alzheimer's disease (AD). The mechanisms leading to the accumulation of these proteins are not completely clear. Hsc-70/Hsp-70, a chaperone protein, has been shown to bind both these proteins and regulate their degradation. We have previously shown that the co-chaperone protein BAG-1 can inhibit the degradation of tau by forming a complex with Hsc-70 and tau. In this current work, we show that there is an increase in the BAG-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 22 publications
2
19
0
1
Order By: Relevance
“…It is unclear why increased expression of BAG-1 result in decreased tau degradation, although the authors suggested it could be due to BAG-1 facilitating the refolding of tau and downregulating the pathway that leads to degradation (Elliott, et al, 2007). This same group also reported that an isoform of BAG-1, BAG-1M is increased in the hippocampi of AD patients (Elliott, et al, 2009). In contrast to these studies we found that increasing BAG3 levels in primary neurons alone resulted in a significant decrease in total and phospho-tau levels.…”
Section: Discussionmentioning
confidence: 71%
“…It is unclear why increased expression of BAG-1 result in decreased tau degradation, although the authors suggested it could be due to BAG-1 facilitating the refolding of tau and downregulating the pathway that leads to degradation (Elliott, et al, 2007). This same group also reported that an isoform of BAG-1, BAG-1M is increased in the hippocampi of AD patients (Elliott, et al, 2009). In contrast to these studies we found that increasing BAG3 levels in primary neurons alone resulted in a significant decrease in total and phospho-tau levels.…”
Section: Discussionmentioning
confidence: 71%
“…Immunoblot analysis was carried out with indicated antibodies, and analysis and quantification were performed by ChemiDoc XRS (Bio-Rad) or by ImageQuant TM TL (General Electrics). Protein from frozen blocks of human hippocampus were obtained from The Netherlands Brain Bank as described previously (28). Proteins were extracted in buffer A (20 mM HEPES, pH 7.4, 0.32 M sucrose, 150 mM KCl, 3 mM MgCl 2 , 10 mM NaF, 20 mM ␤-glycerol phosphate).…”
Section: Methodsmentioning
confidence: 99%
“…For example, Bag-1 interacts with and inhibits the function of the tumor suppressor p73 [8]. Furthermore, the medium isoform, Bag-1M is increased in the hippocampus of Alzheimer's disease patients and binds to Tau protein and amyloid precursor protein (APP), and overexpressed Bag-1M induces increased level of Tau and APP that are related with the pathology and treatment of Alzheimer disease [9,10].…”
Section: Introductionmentioning
confidence: 99%